ANALISIS KEPUASAN PENGGUNA APLIKASI KAMIADA MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Oey, Wilson Jonathan; Zaman, Baizul; Bahri, Syamsul (STMIK KHARISMA Makassar, 2023)
Our Application There is a website application that operates in the field of repair and maintenance services for various kinds of needs. The method used in this research is Importance Performance Analysis (IPA). This research uses primary data sourced from an online questionnaire involving 20 respondents. Based on the results and discussion, the overall average importance value is 3.36, while the overall average performance value is 3.39. In the IPA method, quadrant I has 1 indicator, quadrant II has 1 indicator, quadrant III has 3 indicators, and there are no indicators in quadrant IV. The results of this research can be used as a reference to measure the level of satisfaction of KamiAda application users and, if necessary, improvements to the KamiAda application can be made while paying attention to user needs.